Clinical Cardiac Electrophysiology in Clinical Practice - Huang, MD, David T.; Huang, MD, David T.; Prinzi, MD, Travis.; Prinzi, MD, Travis. (In Clinical Practice, 2015)
This is a practical guide to the clinical diagnosis and treatment of cardiac arrhythmias that meets the needs of this highly specialized, complex and growing field of cardiology. As understanding of the evaluation of treatment of arrhythmias continues to advance, learning and understanding the principles of electrophysiology in order to provide the best possible treatments for patients can be a daunting task. With a scientific, practical, and multi-disciplinary approach, Clinical Cardiac Electrophysiology in Clinical Practice establishes the foundation of the subject and provides a concise illustrative approach to facilitate and enhance understanding. It is designed to be accessible to serve as an introduction to electrophysiology, but advanced enough to serve as a guide for experienced practitioners. Electrophysiology students of all levels, including residents, fellows, mid-level providers, nurses, technologist, primary care providers, cardiologists and electrophysiologists will find value in these pages.